Electrochemical chlorine sensor based on the halide electrolyte with mediator for accidental releases - Букет, Александр Иванович; Линючева, Ольга Владимировна; Нагорный, Алексей Викторович; Линючев, Алкесандр Генадиевич (Eastern-European Journal of Enterprise Technologies, 2014)
An amperometric chlorine sensor with matrix electrolyte based on LiI, surpassing existing domestic and foreign samples by a range of specifications was developed. Implementation of the gas diffusion indicator electrode with iodine-iodide mediator system has allowed to increase the upper limit of measurement by more than an order of magnitude. Optimization of the indicator electrode with regard to the background current has allowed to expand the measurement range by 7 times compared with existing samples, which with the possibility of the 0,17 ppm chlorine concentration measurement (at the maximum allowable concentration of 0,3 ppm) allows to reach the upper limit of measurement of 100 ppm or more. The duration of the transition process (τ90) of defining the transitional signal of the developed sensor is within 30-60s. Balanced electrochemical system of the sensor ensures its stable operation by several times longer than the warranty period.